Scattering of 15C on 208Pb at energies near the Coulomb barrier: Study of the experimental device response via the 12C+208Pb scattering - Távora V.G.; Ovejas J.D.; Martel I.; Tengblad O.; Borge M.J.G.; Acosta L.; Kurtukian-Nieto T.; Sánchez-Benítez A.M.; di Pietro A.; Figuera P.; Keeley N.; Rusek K. (EPJ Web of Conferences, 2023)
There are evidences that the 15C nucleus has an extended neutron distribution or a "neutron halo", but this situation is far from clear. If 15C has 1n-halo, the scattering dynamics should be affected and the angular distribution of the elastic channels should be sensitive to coupling effects due to the halo configuration. The objetive of this study is to understand the role of the halo in 15C by investigating its dynamical response in intense electric fields at energies close to the Coulomb barrier. For this purpose experiment IS619 was conducted performing the 15C + 208Pb elastic scattering reaction at HIE-ISOLDE, CERN. The beam energy was 4.37 MeV/u, which is very close to the Coulomb barrier of the system. The experimental setup used was the global detection system GLORIA, a six silicon telescopes array enable to measure the energy and angular distributions of the scattered particles. During the experiment, the 12C+208Pb scattering at 4.37 MeV/u was measured for calibration. The results of the 12C+208Pb measurement were used to fine-tune the geometry of the experimental setup and it is presented in this contribution.